Promoting employee intention to stay: do human resource management practices matter? - Johari, Johanim; Tan, Fee Yean; Adnan, Zurina; Yahya, Khulida Kirana; Ahmad, Mohamad Nassruddin (Universiti Putra Malaysia, 2012)
The main objective of this study is to assess the predicting role of human resource management (HRM) practices on employee intention to stay. Four dimensions of HRM practices examined in this study are training and development, career development, compensation and benefits, and performance appraisal. A survey was conducted among employees in manufacturing companies in the Northern Region of Peninsular Malaysia. A total of 184 questionnaires were returned and used for data analysis. Based on the statistical tests conducted, the findings reported that only compensation and benefits had a positive impact on respondents’ intention to stay. Discussions elaborated on the importance of compensation and benefits in promoting intention to stay among respondents. Finally, recommendations and conclusion were also highlighted.